Communications Strategic Intent With Systemigrams: Application to the Network-Enabled Challenge - Blair, Charles; Boardman, John; Sauser, Brian (Systems Engineering, 2007)
The U.K. Ministry of Defense (MoD) has mandated the development of a network enabled capability (NEC) across all of defense, aimed at producing agile military and nonmilitary effects via a network of networks. This paper provides an overview of NEC, representing it as a complex human activity system of systems (SoS), analysis of which cannot rely on purely traditional reductionist engineering approaches, requiring instead a soft-systems engineering approach. A literature review is then provided, covering nontraditional systems methodologies of the past 25 years, highlighting the more recent trend towards multimethodological practice. The paper introduces the systemic diagram, or systemigram, conceptual model, explaining its evolution from a form of visual language to its use as an appreciative learning system in a soft-systems methodology. Using the written prose of MoD policy makers, a systemigram model is constructed which represents the NEC concept, providing a systemic visualization of its complexity and an elucidation of the key SoS attributes of emergence, hierarchy, and boundary. Finally, the NEC systemigram is used in an example storyboarding technique, demonstrating its utility as a platform for stakeholder dialog leading towards a refined model that reflects a deeper understanding of NEC strategy. © 2007 Wiley Periodicals, Inc. Syst Eng 10:309–322, 2007

Making Outcome Mapping Work - Evolving experiences from around the World - Jones, Harry (Outcome Mapping Learning Community, 2007)

From PRA to PLA and pluralism: practice and theory - Chambers, Robert (IDS, 2007)
PRA (participatory rural appraisal) and the more inclusive PLA (participatory learning and action) are families of participatory methodologies which have evolved as behaviours and attitudes, methods, and practices of sharing. During the 1990s and 2000s PRA/PLA has spread and been applied in most countries in the world. Among the multifarious domains of application, some of the more common have been natural resource management and agriculture, programmes for equity, empowerment, rights and security, and community-level planning and action. Related participatory methodologies which have co-evolved and spread widely as movements include farmer participatory research, Integrated Pest Management, Reflect, Stepping Stones and Participatory Geographic Information Systems. Ideologically and epistemologically PRA/PLA seeks and embodies participatory ways to empower local and subordinate people, enabling them to express and enhance their knowledge and take action. It can be understood as having three main components: facilitators’ behaviours, attitudes and mindsets linked with precepts for action; methods which combine visuals, tangibles and groups; and sharing without boundaries. The interplay of these resonates with theories of chaos, complexity, emergence and deep simplicity, especially self-organising systems on the edge of chaos. Good practice has moved towards an eclectic pluralism in which branding, labels, ownership and ego give way to sharing, borrowing, improvisation, creativity and diversity, all these complemented by mutual and critical reflective learning and personal responsibility. Keywords: participatory methodologies; networks; pluralism; practice; theory.